Uji Kesesuaian Hasil Pemeriksaan Sedimen Urine Metode Shih-Yung pada Volume Urine 10 mL dan 5 mL - Putri Niawaty; Rikarni Rikarni; Dwi Yulia (Jurnal Kesehatan Andalas, 2021)
Microscopic examination of urine sediment using shih-yung system requires 10ml urine volume. Pediatric patients and kidney disease patients with oliguria difficult to get 10mL urine samples, so it needs to be studied to determine the accuracy of results with smaller sample volumes. Objectives: To analyze agreement of urine sediment examination using Shih-yung system in 10 mL and 5 mL urine volume. Methods: This study was a cross-sectional analysis of 37 urine specimens that met inclusion and exclusion criteria at the central laboratory of Dr. M. Djamil Hospital from July to September 2020. Examination of erythrocyte sediment, leukocyte sediment, and non-hyaline cast using Shih-yung system was done in 10 mL and 5 mL urine volume. Data were analyzed using kappa reliability/agreement test and significant if p<0.05. Results: Agreement test of erythrocyte sediment examination using Shih-yung system in 10ml and 5mL urine volume were moderate significantly (κ=0.600; p<0.05), agreement of leukocyte sediment examination were moderate significantly (κ=0.571; p<0.05), and agreement of nonhialin cast examination were substantial significantly (κ=0.767; p<0.05). Conclusion: Agreement test of erythrocyte and leukocyte sediment examination in 10ml and 5mL urine volume is moderate, so 5ml urine volume was not recommended. Manual examination with microscope and difference in urine sample volume causing difference sediment concentration and amount of sediment per microscope field of view.Keywords: Shih-yung,  urine sediment,  urine volume